Peran Kepuasan Kerja dan Motivasi dalam Memediasi Pengaruh Pemberian Tambahan Penghasilan Pegawai (TPP) Terhadap Kinerja Pegawai BKPSDM Kabupaten Konawe Selatan - Zulkifli; Muh. Nur; Mahmuddin A. Sabilalo (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The study aims to determine the role of job satisfaction and motivation in mediating the effect of employee income supplement (TPP) on employee performance at the Konawe Selatan Regency BKPSDM. The research method used was a quantitative approach. Data were collected using questionnaires and documentation studies. The data analysis technique used is Structural Equation (Smart PLS). The results of this study indicate that employee income supplement (TPP) has a significant effect on employee performance at the Konawe Selatan Regency BKPSDM. Employee income supplement (TPP) has a significant effect on employee job satisfaction at the Konawe Selatan Regency BKPSDM. Employee income supplement (TPP) has a significant effect on employee motivation at the Konawe Selatan Regency BKPSDM. Job satisfaction has a significant effect on employee performance at the Konawe Selatan Regency BKPSDM. Motivation does not have a significant effect on employee performance at the Konawe Selatan Regency BKPSDM. Job satisfaction does not have a significant mediating effect in employee income supplement (TPP) on employee performance at the Konawe Selatan Regency BKPSDM. Motivation does not have a significant mediating effect on the provision of additional employee income (TPP) on the performance of BKPSDM employees of South Konawe Regency